Fostering Islamic Leadership Skills in Students Through Training Activities - Budiharjo, El Fikry; Astutik, Anita Puji (Universitas Muhammadiyah Sidoarjo, 2024)
Background: Qualitative research focuses on naturalistic and phenomenological observations to explore complex issues. Specific Background: This study investigates the leadership development of high school students in the Basic Leadership Training (LDKS) program through direct observation. Knowledge Gap: Previous studies lack in-depth analysis of LDKS's specific processes and effectiveness in shaping students' leadership character. Aims: The research aims to uncover the effectiveness of LDKS by observing participant activities and interactions. Results: Findings indicate that LDKS enhances key leadership qualities such as communication, teamwork, decision-making, and responsibility through structured activities and peer learning. Novelty: This study employs thematic analysis of observational data to reveal nuances in leadership character formation within education. Implications: Results suggest LDKS effectively cultivates leadership skills, providing insights for educators and policymakers focused on character development in educational settings. Highlights : Direct Observation: Employs direct observation to capture real-time interactions and activities during LDKS. Key Qualities: Focuses on developing essential leadership qualities such as communication and teamwork. Educational Impact: Provides insights for educators on effective character development interventions. Keywords: qualitative research, leadership development, Basic Leadership Training, student character formation, thematic analysis